The Effect Of Person-Job Fit, Leadership Traits, And Proactive Personality On Work Productivity With Growth Mindset As A Moderation In Manufacturing Companies In Tangerang City - Heryanto Heryanto; Sihar Tambun (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Employee work productivity is a crucial factor in enhancing the competitiveness of manufacturing companies amidst increasingly dynamic industrial developments and global competition. However, employee work productivity remains a challenge for manufacturing companies in Tangerang City due to the mismatch between work and individual abilities, suboptimal leadership characteristics, and low levels of employee proactiveness. Furthermore, a growth mindset is considered capable of strengthening an individual's ability to face challenges and improve work quality. This study aims to analyze the influence of person-job fit, leadership traits, and proactive personality on work productivity, with growth mindset as a moderating variable. The study used a quantitative approach with a survey method by distributing questionnaires to 260 employees of manufacturing companies in Tangerang City. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that person-job fit, leadership traits, and proactive personality had a positive and significant effect on work productivity. Growth mindset was able to moderate the relationship between person-job fit and proactive personality on work productivity, but was unable to moderate the relationship between leadership traits and work productivity. These findings provide important implications for human resource management in the manufacturing sector.